Educating Emotions: An instrument to work on “feelings of guilt” - Laorden Gutiérrez, Cristina (Pulso. Revista de educación, 2005)
The emotional aspect in education is increasingly becoming more important as a part of the teacher‘s training programme as well as within educational practice. Such importance is acknowledged in this article; besides, some current trends about the general topic are commented and, specifically, one particular emotion- the feeling of guiltiness- which is related to other psychological topics such reasoning and behaviour. Finally, it is presented a device which may help and guide teachers interested in analyzing and assessing this emotional aspect; starting from five context situations which will lead the pupil to reflect on his/her feelings and the teachers to reach conclusions to modify inappropriate behaviour